First‐Dose Methylphenidate‐Induced Changes in the Anti‐Saccade Task Performance and Outcome in Adults with Attention‐Deficit/Hyperactivity Disorder. Issue 4 (19th May 2021) - Duval, Fabrice; Erb, Alexis; Mokrani, Marie‐Claude; Weiss, Thomas; Carcangiu, Roberta
Abstract : Objective: We examined whether the anti‐saccade task (AST) performance after the first methylphenidate (MPH) dose could be associated with subsequent clinical outcome in adults with attention‐deficit/hyperactivity disorder (ADHD). Methods: Ninety‐seven drug‐naive DSM‐5 ADHD adults participated in this study. The AST parameters were measured at baseline, after the first MPH‐dose (10 mg orally), and 6 months after chronic MPH treatment. Results were compared with those of 50 healthy control (HC) subjects. Results: At baseline, ADHDs showed longer saccadic reaction times and more direction errors than HCs (both p < 0.00001). Acute and chronic MPH administration resulted in normalization of the AST performances. Multivariate regression analysis after adjusting for age, sex, weight, and severity of symptoms at baseline, revealed that a low percentage of direction errors after the first MPH‐dose (i.e., ≤10%) could predict remission at month 6 (OR: 5.84; 95% CI: 2.00–17.11; p = 0.001). Conclusions: Our findings indicate that: (1) impairments of motor planning and response inhibition in adults with ADHD are improved with MPH, and (2) a low direction error percentage after the first MPH‐dose may be an independent predictor of remission. ClinicalTrials.gov identifier: NCT03411434 HIGHLIGHTS: The antisaccade task (AST) is useful to reveal impairments in inhibitory control in ADHD. Never‐medicated adult ADHD subjects show delays in reaction times and increased direction errors. Methyphenidate (MPH) administration, either acute or chronic, normalizes AST performances. Direction error percentages after the first MPH‐dose could predict treatment outcome.